2019
DOI: 10.1093/pubmed/fdz003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of metabolic syndrome in Spanish salaried workers: evidence from 15 614 men and women

Abstract: Objective To describe the prevalence of Spanish workers with Metabolic Syndrome (MetS) and those at risk of developing MetS in 2015. Methods Cross-sectional study of workers (n = 15 614). We used a modified definition of the NCEP:ATPIII criteria for MetS (we used body mass index (BMI) above 28.8 kg/m2 instead of the waist circumference criterion). We calculated the prevalence of MetS (having at least three components) and of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The prevalence of MS, as defined by ATP-III criteria, observed in the present analysis is similar to that observed in previously published Spanish studies on the adult working population [4,5,22]. Similarly to ours, these studies also observed that the prevalence of MS was higher in men than women, increased with age, and was greater in the lower social classes as compared to the higher [4,5,22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of MS, as defined by ATP-III criteria, observed in the present analysis is similar to that observed in previously published Spanish studies on the adult working population [4,5,22]. Similarly to ours, these studies also observed that the prevalence of MS was higher in men than women, increased with age, and was greater in the lower social classes as compared to the higher [4,5,22].…”
Section: Discussionsupporting
confidence: 91%
“…Specific to the Spanish population, a study carried out in adults aged 35–74 years showed a higher prevalence of MS in men up to 55 years of age and in women over the age of 65, who also presented a higher coronary risk associated with the presence of MS [ 21 ]. MS prevalence in the working population, which overall was estimated to be 10.2% by the Modified National Cholesterol Education Program Adult Treatment Panel-III (NCEP-ATP III) criteria [ 5 ], was significantly higher among men than women [ 4 , 5 , 22 , 23 ] and among older workers and those in the lower SES [ 4 , 5 , 22 ]. However, when looking at MS prevalence in relation to SES in men and women separately, information is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The PSM is used to balance the distribution of covariates between two observed groups to reduce selection bias [ 42 ]. We reviewed previous studies [ 43 , 44 ], conducted the basic analysis and conducted nearest neighbor matching with caliper 0.2. The four general characteristics variables used were age, marital status, level of education, and salary.…”
Section: Methodsmentioning
confidence: 99%